THE EFFECT OF ROUTINE DYNAMIC WARM-UP MODIFICATION ON SPEED, AGILITY, AND MUSCLE ENDURANCE IN AMATEUR FEMALE FOOTBALL ATHLETES - Arfiansyah, Eggy Nur; Putri, Rintania Rahma (Stadium - Hungarian Journal of Sport Sciences, 2024)
Football prioritizes physical aspects such as speed, agility, strength, flexibility, and muscle endurance. With women's growing interest in football in Indonesia, it is becoming increasingly clear that an excellent physical condition is necessary. Therefore, good physical condition will also impact the risk of injury and, most importantly, performance on the field. Thus, the main aim of this study was to evaluate the effects of Dynamic Warm-Up modification for six weeks on several physical performances, such as (running, change of direction speed, and muscle endurance) in female amateur soccer players. This prospective study involved a modified routine dynamic warm-up program intervention, three times a week warming up before the training session with details of the intervention implementation time, namely 18 times, excluding the initial and final tests. At the start, the players demonstrated dexterity and tests of speed, agility, and muscle endurance, and the test was carried out again at the end of the program intervention. The results show that the significance value of the 30 m Sprint test is 0.083 > 0.05, meaning there is no program influence on the speed component. Furthermore, the significance value of the Illinois Agility test is 1,000 > 0.05, meaning the program does not influence the agility component. Then, the significance value of the wall sit test is 0.083 > 0.05, meaning that the program does not influence the agility component. This study concluded that modifying the dynamic warm-up routine could not improve physical performance, namely speed, agility, and muscle endurance in female soccer players.